Analisis Pemahaman Konsep Matematika Siswa Sekolah Menengah Pertama yang Mengalami Math Anxiety - Lisnawati; Astuti, Reni; Sandie, Sandie (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
This study was motivated by the low quality of Indonesian students' mathematical concept understanding, as shown by the PISA 2022 results, and by preliminary observations at SMP Mujahidin Pontianak indicating a relationship between the level of math anxiety and students' conceptual understanding ability. This study aimed to (1) describe the mathematical concept understanding ability of junior high school students experiencing math anxiety, (2) analyse the relationship between the level of math anxiety and mathematical concept understanding, and (3) identify the factors causing math anxiety among junior high school students. A descriptive qualitative approach was employed. The research subjects were eighth-grade students of SMP Mujahidin Pontianak in the 2025/2026 academic year, selected based on their level of math anxiety (high, moderate, and low). Data were collected through a questionnaire, a concept-understanding test on the topic of circles, and in-depth interviews, then analysed through data reduction, data display, and conclusion drawing/verification. The results revealed a consistent pattern: the higher the students' math anxiety, the lower their conceptual understanding, particularly on the interpretation and extrapolation indicators. Students with low anxiety demonstrated the most comprehensive understanding, those with moderate anxiety showed fairly good but inconsistent understanding, while students with high anxiety experienced serious cognitive obstacles. Three interrelated factors causing math anxiety were identified: personality (psychological/emotional), intellectual, and environmental/social factors, which jointly influenced the intensity of students' math anxiety. These findings suggest that teachers need to address the somatic, cognitive, and attitudinal dimensions of anxiety simultaneously while strengthening students' interpretation and extrapolation skills through supportive, anxiety-reducing instructional strategies.